A prospective study of adverse effects of antipsychotics in adolescents with schizophrenia during a 6-month follow-up. (January 2019) - Ulloa, Rosa E.; Pérez-Garza, Rodolfo; Arce, Sofía; Bermúdez, Yvanna; Palacios, Lino
Abstract : There is a paucity of follow-up studies of neurological, endocrine, and metabolic adverse effects of antipsychotics in adolescents from low-income and middle-income countries, who have a higher prevalence of obesity and overweight, and could present increased morbidity. A Mexican sample of 86 adolescents with schizophrenia was examined during a 6-month follow-up using the Simpson–Angus, abnormal involuntary movement and Barnes Akathisia rating scales, in addition to a side effects score sheet and other laboratory measures. Binary logistic regression models were used to identify specific variables as predictors of weight gain. Sleep difficulties, restlessness, drowsiness, changes in thyroid hormones, and a linear increase in weight gain were observed. A baseline positive and negative syndrome scale score greater than 97 predicted a 5 kg increase at month 3 (odds ratio: 4.52, 95% confidence interval: 1.5–13.2). The absence of a plateau in weight gain in the present study across the 6-month treatment period and its relationship with illness severity suggests that even longer follow-up time should be examined in future studies in these patient populations.